2017
DOI: 10.1007/s12393-017-9162-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed Electric Fields Processing Strategies on Health-Related Compounds of Plant-Based Foods

Abstract: In the last decades, pulsed electric fields (PEF) have been proposed as alternative or complementary to traditional food processing technologies in order to improve the competitiveness of the food industry. PEF has been suggested as a technology of choice to obtain safe and high-quality plant-based foods with a shelf-life similar to the attained with mild heat pasteurization treatments. On the other hand, the application of PEF as a pretreatment for the permeabilization of vegetable tissues has been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…2). The complexity and diversity of polyphenols (molecular size and structure) makes it difficult to anticipate the effect of electric field (Elez-Martínez et al, 2017). Therefore, the following results consider the extraction of individual polyphenols, mainly three relevant polyphenolic compounds that were found to be present: naringenin, rutin and kaempferol.…”
Section: Electric Field Effects On Bc Extraction From Tomatomentioning
confidence: 99%
“…2). The complexity and diversity of polyphenols (molecular size and structure) makes it difficult to anticipate the effect of electric field (Elez-Martínez et al, 2017). Therefore, the following results consider the extraction of individual polyphenols, mainly three relevant polyphenolic compounds that were found to be present: naringenin, rutin and kaempferol.…”
Section: Electric Field Effects On Bc Extraction From Tomatomentioning
confidence: 99%
“…However, to reach these levels of enzyme inactivation large specific energies (1,066–44,000 kJ/L) are required, while only 50–1,000 kJ/kg are sufficient for microbial inactivation (78). More recently, numerous studies have reported that PEF-pasteurization of plant-based beverages at mild temperatures can minimize changes in their physicochemical characteristics (e.g., pH, color, aroma, and flavor) and can significantly improve the nutritional properties of beverages due to retention of higher amounts of health-related biomolecules (e.g., vitamins, polyphenols, carotenoids…), as compared to thermal processing (52, 7981). Despite the large quantity of scientific data available in the literature about the benefits of PEF processing and various technology transfer projects, there is still very little industrial implementation of PEF for pasteurization of liquids, and it is primarily limited to waste water treatment (82).…”
Section: Non-thermal Stabilizationmentioning
confidence: 99%
“…On the other hand, PEF induces plant response to abiotic stress, e.g., enhancing the secondary metabolism with the accumulation of phenolic compounds in plant tissue (Elez-Martínez, Odriozola-Serrano, Oms-Oliu, Soliva-Fortuny, & Martín-Belloso, 2017). It is very likely that the underlying mechanisms of the occurrence of both effects are independent from each other.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…During post-harvest management, food processing can be used in an innovative way to protect or enhance the apple phenolic content, in the pursuit of apple products with higher functional value (Ribas-Agustí, Martín-Belloso, Soliva-Fortuny, & Elez-Martínez, 2017). In this sense, pulsed electric fields (PEF) have gained interest, as they achieve microbial inactivation with less decline in bioactive compounds and quality attributes, with respect to conventional thermal treatment (Elez-Martínez, Odriozola-Serrano, Oms-Oliu, Soliva-Fortuny, & Martín-Belloso, 2017).…”
Section: Introductionmentioning
confidence: 99%